2022
DOI: 10.1159/000521890
|View full text |Cite
|
Sign up to set email alerts
|

Serum Eosinophilic Cationic Protein Is a Reliable Biomarker for Childhood Asthma

Abstract: <b><i>Background:</i></b> Eosinophilic cationic protein (ECP) is associated with airway inflammation and asthma. However, the clinical value of measuring ECP in childhood asthma is not fully known. We aimed to study the diagnostic performance of serum ECP and other common asthma biomarkers, individually and in combinations. <b><i>Methods:</i></b> In a cross-sectional study, 5–16-year-old children with current asthma (CA) (<i>n</i> = 37), transient ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…These results demonstrate that the sampling method is critical in proteomic experiments. In addition, the level of ECP is consistent with it being an important protein in eosinophil-mediated allergic inflammation such as asthma [ 42 , 43 ] and chronic rhinosinusitis [ 44 ].…”
Section: Proteomics Approaches In Respiratory Allergymentioning
confidence: 91%
“…These results demonstrate that the sampling method is critical in proteomic experiments. In addition, the level of ECP is consistent with it being an important protein in eosinophil-mediated allergic inflammation such as asthma [ 42 , 43 ] and chronic rhinosinusitis [ 44 ].…”
Section: Proteomics Approaches In Respiratory Allergymentioning
confidence: 91%
“…In a population-based study with 259-animal sensitized, most were sensitized to two or more dog allergens, and co-sensitization to Can f 5 [prostate (i.e., male) specific allergen] and Can f 1/2 conferred the greatest risk for asthma [ 124 ]. In line with this, a recent study in children with mild to severe asthma showed that sensitization to a greater number of dog components may identify children whose asthma severity is driven by dog exposure and may benefit from targeted interventions such as exposure mitigation and immunotherapy [ 125 ]. To this end, molecular-based allergy diagnostics such as CRD provides clinicians with opportunities to better characterize children with polysensitization [ 126 ].…”
Section: The Wheezing Child: a Paradigm To Optimize Asthma Control In...mentioning
confidence: 98%